Air Pollution and Health Effects - Nadadur, Srikanth S (Springer, 2015)
The health effects of air pollution were recognized after the Industrial Revolution with a transition to manufacturing processes that utilize fuel burning and the emergence of large and densely populated cities. One of the first reports highlighting the health effects of air pollution described the experience in London in 1952 where increased coal burning for heat resulted in dense smog that engulfed the city (Logan 1953, 1956). During a brief period of time, approximately 12,000 excess deaths were associated with increased levels of smog. This incident represents one of the first reports linking level of ambient air pollution and excess mortality. This epidemiological observation contributed to the passing of the Clean Air Act in 1956 by the Parliament of the United Kingdom, which began the process of eliminating the burning of coal in homes and in factories in England. Numerous scientific reports have followed supporting the notion that adverse health effects are associated with exposure to ambient air pollution. In an effort to protect public health and welfare, the US Clean Air Act was passed in 1970, which mandated setting national ambient air quality standards for specific common and widespread pollutants based on the latest science. Similarly the World Health Organization currently provides recommendations with regard to ambient air quality standards in an effort to protect global health and well-being. The body of literature supporting the broad health effects of ambient air pollution is expansive. The overall goal of this book is to highlight the weight of scientific evidence supporting our current understanding of the impact of air pollution on human health...